Cumulative Fluid Balance and Mortality in Septic Patients With or Without Acute Kidney Injury and Chronic Kidney Disease*. Issue 10 (October 2016) - Neyra, Javier A.; Li, Xilong; Canepa-Escaro, Fabrizio; Adams-Huet, Beverley; Toto, Robert D.; Yee, Jerry; Hedayati, S. Susan
Abstract : Objective: Incident acute kidney injury and prevalent chronic kidney disease are commonly encountered in septic patients. We examined the differential effect of acute kidney injury and chronic kidney disease on the association between cumulative fluid balance and hospital mortality in critically ill septic patients. Design: Retrospective cohort study. Setting: Urban academic medical center ICU. Patients: ICU adult patients with severe sepsis or septic shock and serum creatinine measured within 3 months prior to and 72 hours of ICU admission. Patients with estimated glomerular filtration rate less than 15 mL/min/1.73 m 2 or receiving chronic dialysis were excluded. Interventions: None. Measurements and Main Results: A total of 2, 632 patients, 1, 211 with chronic kidney disease, were followed up until hospital death or discharge. Acute kidney injury occurred in 1, 525 patients (57.9%), of whom 679 (44.5%) had chronic kidney disease. Hospital mortality occurred in 603 patients (22.9%). Every 1-L increase in cumulative fluid balance at 72 hours of ICU admission was independently associated with hospital mortality in all patients (adjusted odds ratio, 1.06 [95% CI] 1.04–1.08; p < 0.001), and in each acute kidney injury/chronic kidney disease subgroup (adjusted odds ratio, 1.06 [1.03–1.09] for acute kidney injury+/chronic kidney disease+; 1.09 [1.05–1.13] for acute kidney injury–/chronic kidney disease+; 1.05 [1.03–1.08] for acute kidney injury+/chronic kidney disease–; and 1.07 [1.02–1.11] for acute kidney injury–/chronic kidney disease–). There was a significant interaction between acute kidney injury and chronic kidney disease on cumulative fluid balance ( p =0.005) such that different cumulative fluid balance cut-offs with the best prognostic accuracy for hospital mortality were identified: 5.9 L for acute kidney injury+/chronic kidney disease+; 3.8 L for acute kidney injury–/chronic kidney disease+; 4.3 L for acute kidney injury+/chronic kidney disease–; and 1.5 L for acute kidney injury–/chronic kidney disease–. The addition of cumulative fluid balance to the admission Sequential Organ Failure Assessment score had increased prognostic utility for hospital mortality when compared with Sequential Organ Failure Assessment alone, particularly in patients with acute kidney injury. Conclusions: Higher cumulative fluid balance at 72 hours of ICU admission was independently associated with hospital mortality regardless of acute kidney injury or chronic kidney disease presence. We characterized cumulative fluid balance cut-offs associated with hospital mortality based on acute kidney injury/chronic kidney disease status, underpinning the heterogeneity of fluid regulation in sepsis and kidney disease.